2021
DOI: 10.3390/nu13041118
|View full text |Cite
|
Sign up to set email alerts
|

Food Fortification: The Advantages, Disadvantages and Lessons from Sight and Life Programs

Abstract: Deficiencies in one or more micronutrients such as iron, zinc, and vitamin A are widespread in low- and middle-income countries and compromise the physical and cognitive capacity of millions of people. Food fortification is a cost-effective strategy with demonstrated health, economic and social benefits. Despite ongoing debates globally and in some countries regarding the performance and safety of food fortification, the practice offers significant benefits across each of the main vehicles for food fortificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 45 publications
1
126
1
1
Order By: Relevance
“…A potentially nutrient improving intake strategy for enriching our diet with specific elements is food fortification [5]. Methods that offer meaningful solutions include classical, Plants 2021, 10, 2275 2 of 17 industrial, large-scale fortification and enhancement through genetic engineering [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…A potentially nutrient improving intake strategy for enriching our diet with specific elements is food fortification [5]. Methods that offer meaningful solutions include classical, Plants 2021, 10, 2275 2 of 17 industrial, large-scale fortification and enhancement through genetic engineering [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…LSFF is increasingly recognized as a cost-effective approach to improve population micronutrient status and related health outcomes [6,7,19]. This study identified factors that inhibited countries with evidence of an elevated potential risk of zinc deficiency from introducing zinc as a fortificant, as well as factors that facilitated countries to include zinc in their fortification program.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of fortification has been successfully conducted for zinc, iron, selenium, vitamin A, vitamin B complexes (e.g., folate, niacin, thiamine), vitamin C, vitamin D and vitamin E [72] enrichment of foods. It is now well accepted that micronutrient fortification of foods has the potential to significantly increase serum micronutrient concentrations, reduce the incidence of micronutrient deficiencies in public health (e.g., Pellagra, Beriberi, childhood rickets, xerophthalmia), reduce clinical manifestations of deficiencies (including goiter, anemia and neural tube defects), and improve overall nutritional status [73,74].…”
Section: Food Fortificationmentioning
confidence: 99%